Review paperOver a decade treating hepatocellular carcinoma percutaneously with radiofrequency thermal ablation. Worldwide experience - Thanos, Loukas; Mylona, Sofia; Ptohis, Nikolaos; Sotiropoulou, Eva; Pomoni, Anastasia; Pomoni, Maria (Archives of Medical Science, 2007)
Hepatocellular carcinoma (HCC) is a very common malignancy. Early diagnosis plays a significant role in the management of patients, affecting survival and prognosis. Surgical resection is the treatment of choice; yet only a small number of patients are surgical candidates at the time of diagnosis. Furthermore, recurrences are very common even after a successful resection. These reasons urged the need to introduce a minimally invasive technique that can be repeated, without the fear of increasing mortality, morbidity, hospitalization and treatment-related cost. In the present article we present our long-standing experience regarding radiofrequency thermal ablation (RFA) treatment of HCC. Indications, clinical results from other investigators and complications are discussed. Additionally there is a description of the technique and the equipment used.